Alternatives to cartography - Craenenbroeck, Jeroen van, 1976- (Studies in generative grammar ;, 2009)
This volume brings together a number of researchers working on non-cartographic conceptions of word order, movement and/or phrase structure. The proposals made in this book discuss both problems for standard cartographic theory as well as alternatives. As such, this book is the first to present a varied and in-depth overview of the position taken by a substantial number of researchers in the field today on what is presumably one of the most hotly debated and controversial issues in present-day generative grammar.